2012
DOI: 10.15292/geodetski-vestnik.2012.04.826-837
|View full text |Cite
|
Sign up to set email alerts
|

Digital terrain models and mathematical modelling of debris flows

Abstract: IZVLEČEK ABSTRACT Mathematical modelling is a common approach when assessing debris-flow hazards. In this study on the mathematical modelling of debris flows, we applied the widely used Flo2D model. The high accuracy of the input parameters is essential for obtaining acceptable results. The numerical grid in the area of the debrisflow movement is generated from topographic data. The aim of our research was to assess the usefulness of public data for debris flow-modelling and to compare this data to the DEM5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…This was due to the substantial negative value of the MD, as shown in Table 2. The inaccuracy of the results obtained adopting the TINITALY DEM was consistent with the ones obtained by Sodnik et al 2012 [46] adopting public DEMs. This outcome could help the flood modelers to understand the limitation of using largely and freely available DEMs, usually affected by systematic errors, in small basins characterized by relatively narrow floodplain that would require detailed topography.…”
Section: Inundation Modeling and Mapping Comparisonsupporting
confidence: 89%
See 1 more Smart Citation
“…This was due to the substantial negative value of the MD, as shown in Table 2. The inaccuracy of the results obtained adopting the TINITALY DEM was consistent with the ones obtained by Sodnik et al 2012 [46] adopting public DEMs. This outcome could help the flood modelers to understand the limitation of using largely and freely available DEMs, usually affected by systematic errors, in small basins characterized by relatively narrow floodplain that would require detailed topography.…”
Section: Inundation Modeling and Mapping Comparisonsupporting
confidence: 89%
“…LiDAR DEMs are usually characterized by high vertical accuracy (e.g., 0.1-0.2 m of RMSE) that is considered comparable with the sensors' noise generated by the microtopographic features [54]. For this reason, LiDAR can be considered a good benchmark for comparing the performances of flood simulations derived from other DEM sources [46].…”
Section: Dems Comparisonmentioning
confidence: 99%
“…DMV 5 was chosen for our project over the DMV 12.5 because of better spatial resolution, although some of the past studies showed that both elevation models are useless for more precise mathematical modelling (e.g. Sodnik et al, 2009). Since this paper describes complete torrents, from springs to confluences with larger streams, good approximations of the longitudinal profiles can be obtained already by using DMV 5 (Mohorič, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The Bela torrential fan was classified as a transitional fan, where debris flows are possible. For debris flow modelling, a Flo 2-dimensional model was used with different numerical square grids generated from digital elevation models (Sodnik et al, 2009(Sodnik et al, , 2012(Sodnik et al, , 2013Sodnik & Mikoš, 2018;Bezak et al, 2020). The calculated results showed that the estimated inundated area ranges between 118 and 145 m² and the average maximum flow depth ranges from 0.6 to 1.2 m, depending on the square grid applied.…”
Section: An Overview Of Past Researchmentioning
confidence: 99%